PLASMA SOLUBLE ENDOGLIN CONCENTRATION IN PREECLAMPSIA IS ASSOCIATED WITH AN INCREASED IMPEDANCE TO FLOW IN THE MATERNAL AND FETAL CIRCULATIONS - Chaiworapongsa, Tinnakorn (2010)
OBJECTIVE: To examine the relationship between abnormalities in uterine (UT) and/or umbilical artery (UA) Doppler velocimetry and maternal plasma concentrations of soluble endoglin (sEng), in patients with preeclampsia (PE). METHODS: A cross-sectional study was conducted in normal pregnant women (n=135) and patients with PE (n=69). Patients with PE were sub-classified into four groups: 1) those who had Doppler abnormalities in both the UT and the UA; 2) patients who had Doppler abnormalities in the UT alone; 3) those who had Doppler abnormalities in the UA alone; and 4) patients without Doppler abnormalities in either vessel. Plasma concentrations of sEng were determined by ELISA. RESULTS: Among patients with PE, those with an abnormal UT and UA Doppler velocimetry had the highest median plasma concentration of sEng compared to any other groups (Kruskal Wallis p<0.001). Women with PE with normal Doppler velocimetry in both vessels had the lowest median plasma concentration of sEng. There was a significant relationship between plasma concentrations of sEng and mean UT resistance index (Spearman Rho =0.5; p<0.001) as well as UA pulsatility index (Spearman Rho =0.4; p=0.002). Multiple regression analysis suggested that Doppler abnormalities in the UT/ UA as well as gestational age at blood sampling contributed to plasma sEng concentrations (p<0.001). CONCLUSIONS: Abnormalities of impedance to blood flow in the uterine and umbilical arteries are associated with an excess of sEng in the circulation of mothers with PE. These findings suggest that the “anti-angiogenic state” in PE is partially reflected in abnormalities of Doppler velocimetry.